Approaches to legal regulation on deepfakes in the context of minimising risks and threats to information security of the society and state - Ablameyko, Maria S.; Sukhaparau, Viktar P. (Journal of the Belarusian State University. Law, 2026)
This article explores the characteristics of deepfakes as a form of inappropriate information. International experience in regulating deepfakes is analysed, and based on this, potential amendments to Belarusian legislation in the information sphere regarding protection against deepfakes are proposed. The authors examine the application of current Belarusian legislation on information, informatisation, and information protection as a form of protection against disinformation arising from the development of artificial intelligence technologies. Given the observed disinformation of the population through the dissemination of deepfakes on online resources and in the media, ways to improve legal protection against deepfakes are proposed in the context of ensuring the information security of society and the state.
Keywords: deepfakes; synthetic technologies; content labeling; inappropriate advertising; mass information; information security; protection against disinformation